A contribution to the bryoflora of Mozambique from the 'Google Forest', Mabu Mountain, Zambezia Province. (25th March 2015) - Hedderson, Terry A. J.; Gwynne-Evans, David; Ah-Peng, Claudine; Ribeiro, Daniel
Abstract: Mozambique, with only approximately 82 moss and 54 liverwort species recorded, is among the bryologically most poorly known regions of Africa. We here report on a collection of bryophytes made on Mabu Mountain; a poorly known but biologically rich area of forest in NW Mozambique. The specimens were bulk collections of bryophyte mats made by non-specialists with no attempt to separate or target particular species in the field. Nevertheless, our identifications from this material yielded 56 species (40 mosses and 16 hepatics) of which 43 ( ca 75%) are new records for the country. Given the apparent diversity, as well as the presence of several rare and/or disjunctive species, the bryophytes constitute yet another significant element in the biological richness of the Mabu area, and help highlight its national and regional biological significance. Mabu should be the target of more detailed bryological exploration.